2007
DOI: 10.1152/ajprenal.00246.2006
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection changes glomerular podocyte cytoskeletal composition and results in distinct cellular mechanical properties

Abstract: In addition to forming the selective filtration barrier for the renal glomerulus, podocytes maintain glomerular capillary architecture by opposing distending hemodynamic forces. To understand the relationship of cytoskeletal properties and the mechanical characteristics of podocytes, we studied filamin expression and distribution and measured cell membrane deformability in conditionally immortalized wild-type (WT) mouse podocytes, and in podocytes derived from a mouse model of HIV-associated nephropathy (HIVAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…where fbead is the force on the bead, dcantilever is the deflection of the cantilever measured by the AFM, E is the Young's modulus, v is the Poisson ratio, R is the radius of the bead, and ␦ is the vertical displacement of the cantilever (41). As the external surface of glomeruli is composed primarily of exposed capillaries, the measurements will most likely probe the properties of the external capillary wall.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…where fbead is the force on the bead, dcantilever is the deflection of the cantilever measured by the AFM, E is the Young's modulus, v is the Poisson ratio, R is the radius of the bead, and ␦ is the vertical displacement of the cantilever (41). As the external surface of glomeruli is composed primarily of exposed capillaries, the measurements will most likely probe the properties of the external capillary wall.…”
Section: Methodsmentioning
confidence: 99%
“…AFM probes submicron areas of membrane over a subsecond time scale, and as such, reflects the intrinsic characteristics of a structure since cells and tissues cannot actively remodel their cytoskeletons or membranes over this time scale (41). The external surface of a glomerulus is composed primarily of exposed capillaries, the majority of which are covered by podocyte foot processes as well as some podocyte cell bodies.…”
Section: C400 Elastic Properties Of Glomerulimentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it was shown that conditionally immortalized glomerular podocytes from a mouse model of HIVassociated nephropathy (HIVAN) are substantially softer than normal podocytes (by 25%), as assessed by atomic force microscopy (AFM) and microaspiration (Tandon et al, 2006). At a stage of the disease that showed no detectable pathological changes, the glomeruli from these mice were 30% softer than normal glomeruli (1.5 kPa compared with 2.5 kPa, as measured by AFM) (Wyss et al, 2011).…”
Section: Renal Glomerular Diseasementioning
confidence: 99%